An effective technique based on off‐set fed patch to enhance the bandwidth of microstrip planar antenna. Issue 5 (May 2016) - Azim, R.; Aldhaheri, R. W.; Sheikh, M. M.; Islam, M. T.
ABSTRACT: In this article a microstrip planar antenna with new bandwidth enhancement technique is proposed for broadband wireless communication. The antenna consists of a rectangular radiating patch, a fed line, and a conducting ground plane. To increase the operating band of a conventional microstrip patch antenna, the radiating patch is shifted from the center of the substrate (asymmetric) while the feed line is made as off‐set. It is observed that this asymmetric patch and off‐set feed line improve the impedance matching resulting in a bandwidth enhancement of more than 115% without changing of the overall antenna size. It is observed from the measurement that the proposed planar design with this technique can achieve an operating band ranging from 2.96 to 19GHz (146%) which makes it very suitable for a number of wireless communication applications such as WiMAX, WLAN, UWB, C‐band, X‐band, Ku‐band etc. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1221–1226, 2016